Photosynthetic pigments and gas exchange in red and green cabbage under no-tillage and conventional systems - Echer, Márcia; Guimarães, Vandeir; Inagaki, Adriano; Dalastra, Graciela; Hachmann, Tiago (Revista Ciência Agronômica, 2020)
The aim of the present study was to verify changes in the levels of photosynthetic pigments as well as gas exchange in the Fuyutoyo and Red Cabbage cultivars, grown under no-tillage (NT) and conventional (CT) systems. A randomised block design with four replications was used, in a 2 x 2 factorial scheme, where the Fuyutoyo and Red Cabbage cultivars were evaluated under two tillage systems. The levels of chlorophyll a, chlorophyll b, total chlorophyll and anthocyanins in the leaves were evaluated in triplicate. Localised gas exchange was measured at different times of the day, together with different photosynthetic photon flux density curves (PPFD). The Fuyutoyo cultivar showed a higher mean value for chlorophyll a (34.58%), chlorophyll b (35.09%) and total chlorophyll (34.76%), however, no difference was seen between cultivars for the levels of anthocyanin. Greater mean values for chlorophyll a (76.07%), chlorophyll b (77.87%), total chlorophyll (76.74%) and anthocyanin (72.24%) were found under CT compared to the cultivars grown under NT. The relative chlorophyll content of the Red Cabbage plants was influenced by adoption of the no-till system, showing a higher value for the SPAD index. The Fuyutoyo cabbage cultivar showed greater photosynthetic capacity during the day, promoting greater instantaneous carboxylation efficiency. All the cultivars and tillage systems gave a linear reduction in water use efficiency during this period. Under the conventional system, despite presenting higher rates of stomatal conductance, the Red Cabbage cultivar achieved lower values for net photosynthesis when submitted to light-curve analysis.